Development of Unmanned Aerial Vehicle for Detecting the Forest Fires - Kadıoğlu, Barış Mert; Karatay, Seçil; Çetinceviz, Yücel; Erken, Faruk (Fırat Üniversitesi, 2023)
In recent years, forest fires can be brought under control in line with the information obtained from Unmanned Aerial Vehicles (UAVs), which play an important role in determining the progression of fires, detecting heat points and determining intervention locations. In this study, if the UAV detects the fire by autonomously positioning in the area where the fire is located, the point where the fire reaches the most intense temperature is determined with the help of the thermal camera, and it is ensured that the fireball is dropped to the target with a 100% success rate. The requirements of the UAV, which will be produced in order to realize this task, such as fast, load-carrying and stable flight are also taken into consideration. In addition to being economical and long-lasting of the materials inside, it will be able to fly efficiently in most weather conditions (foggy, dark, etc.). In the construction of the UAV, a domestic Electronic Speed Controller (ESC) with a unique design is produced to meet the sufficient current. With this acquisition, ESC, which will meet the requirements by sending sufficient current to more than one Brushless DC (BLDC) motor, has been tested on our Radio Controlled (RC) aircraft and included in the project.

Son yıllarda yangınların seyrinin belirlenmesinde, ısı noktalarının tespit edilmesinde ve müdahale yerlerinin belirlenmesinde önemli rol oynayan İnsansız Hava Araçları’ndan (İHA) elde edilen bilgiler doğrultusunda orman yangınları kontrol altına alınabilmektedir. Bu çalışmada İHA’nın, yangının bulunduğu bölgede otonom olarak konumlanarak yangını tespit etmesi durumunda, termal kamera yardımıyla yangının en yoğun sıcaklığa ulaştığı nokta belirlenmekte ve ateş topunun %100 başarı oranı ile hedefe düşürülmesi sağlanmaktadır. Bu görevi gerçekleştirmek üzere üretilecek olan İHA'nın hızlı, yük taşıma ve stabil uçuş gibi gereksinimleri de göz önünde bulundurulmuştur. İçerisindeki malzemelerin ekonomik ve uzun ömürlü olmasının yanı sıra çoğu hava koşulunda (sisli, karanlık vb.) verimli bir şekilde uçabilecektir. İHA yapımında yeterli akımı karşılamak için özgün tasarıma sahip yerli Elektronik Hız Kontrol Cihazı (ESC) üretilmiştir. Bu satın alma ile birlikte birden fazla Fırçasız DC (BLDC) motora yeterli akım göndererek gereksinimleri karşılayacak olan ESC, Radyo Kontrollü (RC) uçağımızda test edilmiş ve projeye dâhil edilmiştir.
Orman Yangınlarının Tespiti İçin İnsansız Hava Aracı Geliştirilmesi
Keywords: Embedded Systems; Gömülü Sistemler; Autonomous Vehicle Systems; Otonom Araç Sistemleri